Feeding Iran: Shiʿi families and the making of the Islamic Republic - Wellman, Rose (University of California Press, 2021)
Introduction : kinship, Islam, and the state -- Blood, physio-sacred substance, and the making of moral kin -- Feeding the family : the "spirit" of food in Iran -- Regenerating the Islamic Republic : commemorating martyrs in provincial Iran -- Creating an Islamic nation through food -- Epilogue.